Constitutional and Legal Foundations of Experimental Legal Regimes - I. S. Sushilnikov (Теоретическая и прикладная юриспруденция)
The relevance of the study is due to the importance of the question of the legal nature of such a young institution as an experimental legal regime. The author presents theoretical developments in the field of studying the constitutionality of experimental legal regimes, their relationship with the norms of the Constitution of Russia, dedicated to regulating the principles of a legal, democratic, federal state, support for competition, free use of one’s abilities and property for entrepreneurial and other economic activities not prohibited by law, the unity of economic space on the territory of the Russian Federation, the inadmissibility of restricting constitutional rights and citizens’ freedoms, legality and equality of all before the law. The article analyzes the relationship between the experimental legal regime and the partnership of entrepreneurs and authorities. An attempt is made to analyze the correlation between the experimental legal regime and the delegation of public powers to private individuals. The author, appealing to the judicial practice of the Constitutional Court of the Russian Federation, concludes that the experimental legal regime is based on the articles 1, 3, 8, 19, 29, 34, 55 and 75.1 of the Constitution of Russia.